2007
DOI: 10.2298/jas0702145c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of land use on group and fractional composition of humus in rendzina soils in Serbia

Abstract: The effect of land use on group and fractional composition of humus was examined in 13 rendzina profiles under forests, 12 profiles under grassland and 8 profiles under arable fields in different parts of Serbia where rendzinas are typically found. The difference regarding land use of rendzina soils (depending on cultural practices or absence of any, and different amounts and quality of plant residues) under forest, grassland or arable fields had a highly significant statistical effect on humus group compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Dynamics of some organic matter fractions along altitude cannot be connected with clay size fraction content or pH values of soil. Land use has significant influence on organic matter composition in Rendzinas of Serbia [6]. Rendzinas under forest are dominant on lower altitudes, while on higher altitudes Rendzinas under forest, grassland and arable are equally present, so actual differences in organic matter composition on various altitudes cannot be accredited to direct influence of land use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamics of some organic matter fractions along altitude cannot be connected with clay size fraction content or pH values of soil. Land use has significant influence on organic matter composition in Rendzinas of Serbia [6]. Rendzinas under forest are dominant on lower altitudes, while on higher altitudes Rendzinas under forest, grassland and arable are equally present, so actual differences in organic matter composition on various altitudes cannot be accredited to direct influence of land use.…”
Section: Discussionmentioning
confidence: 99%
“…They are under various forest and grass communities or are cultivated. Hitherto research have shown that carbon content and organic matter composition are influenced by leaching of carbonates and basic cations, and also by the change in land use [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Soil cultivation influenced the structure of arable Rendzinas significantly, causing a decrease of the coefficient of soil structure and stability of structural aggregates (Cupać et al, 2006b). Rendzinas under grass and arable Rendzinas have decreased humus and nitrogen contents (Cupać et al, 2006a), and increased a portion of stable humus, but the same humus type (Cupać et al, 2007).…”
Section: Introductionmentioning
confidence: 99%